2012
DOI: 10.1055/s-0031-1299215
|View full text |Cite
|
Sign up to set email alerts
|

Central Foveal Thickness Before and After Cataract Surgery in Normal and in Diabetic Patients without Retinopathy

Abstract: Eyes of diabetic patients without retinopathy present higher CFT and a higher incidence of CME after cataract surgery on OCT examination compared to eyes of healthy controls. This may explain the unsatisfactory visual acuity following cataract surgery in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
(46 reference statements)
4
15
1
1
Order By: Relevance
“…After cataract surgery, the incidence of postoperative CME revealed on OCT obtained at regular intervals rises to 22% to 28.6% in those with diabetes. 11,12 In contrast to these results, we did not find a statistically significant difference in the rate of CME after DMEK when comparing patients with and without diabetes. This finding is consistent with the results published previously.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…After cataract surgery, the incidence of postoperative CME revealed on OCT obtained at regular intervals rises to 22% to 28.6% in those with diabetes. 11,12 In contrast to these results, we did not find a statistically significant difference in the rate of CME after DMEK when comparing patients with and without diabetes. This finding is consistent with the results published previously.…”
Section: Discussioncontrasting
confidence: 99%
“…Cystoid macular edema (CME) is a well-described complication of intraocular surgery, particularly after cataract surgery, [8][9][10][11][12][13][14] and is detected readily by optical coherence tomography (OCT). 13 The mechanism of postoperative CME is understood incompletely, but may be related to a combination of factors including inflammatory mediators, surgical trauma (particularly to the iris), and vitreomacular traction.…”
mentioning
confidence: 99%
“…5,[12][13][14] Previous studies which analyzed the incidence of ME after cataract surgery in diabetic patients did not differentiate between the incidence of DME and PCME. [15][16][17] To properly treat these eyes, however, it is crucial to classify ME appropriately, as the treatment may vary, depending on the underlying condition. 4,18,19 The aim of this study was to evaluate whether PCME can be differentiated from DME using SD-OCT. For this purpose, SD-OCT images were graded based on our previously established SD-OCT grading protocol to differentiate underlying etiologies in ME.…”
mentioning
confidence: 99%
“…Throughout postoperative follow-up, ten eyes developed CME for a total frequency of 11.6%, irrespective of medication used. Katsimpris et al13 compared central foveal thickness changes after cataract surgery between normal and diabetic patients without retinopathy and found that postoperative central foveal thickness in diabetics at all time-points of the follow-up period was significantly increased compared to controls, and the incidence of CME was 4.0% and 28.6% for controls and diabetics respectively. Also, Tsilimbaris et al14 reported a significant increase in mean foveal thickness in all patients at 1 and 3 months post-cataract surgery, but at 6 months the mean foveal thickness values returned to preoperative levels in the history-free and glaucoma patients, while it remained significantly higher in the diabetic and epiretinal membrane patients.…”
Section: Discussionmentioning
confidence: 99%